Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
( x2 - 4x + 16 )( x + 4 ) - x( x + 1 )( x + 2 ) + 3x2 = 0
<=> x3 + 43 - x( x2 + 3x + 2 ) + 3x2 = 0
<=> x3 + 64 - x3 - 3x2 - 2x + 3x2 = 0
<=> 64 - 2x = 0
<=> 2x = 64
<=> x = 32
( 8x + 2 )( 1 - 3x ) + ( 6x - 1 )( 4x - 10 ) = -50
<=> 2x - 24x2 + 2 + 24x2 - 64x + 10 = -50
<=> -62x + 12 = -50
<=> -62x = -62
<=> x = 1
\(3x\left(x-2\right)-x+2=0\)
\(\Leftrightarrow3x\left(x-2\right)-\left(x-2\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(3x-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-2=0\\3x-1=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=2\\x=\frac{1}{3}\end{cases}}\)
3x^2-5x+2=0
<=>3x2-3x-2x+2=0
<=>3x.(x-1)-2.(x-1)=0
<=>(x-1)(3x-2)=0
<=>x-1=0 hoặc 3x-2=0
<=>x=1 hoặc 3x=2
<=>x=1 hoặc x=2/3
\(3x\left(2x-1\right)-1-2x=0\)
\(\Leftrightarrow6x^2-3x-1-2x=0\)
\(\Leftrightarrow6x^2-5x-1=0\)
chắc bài này sai đề. sửa lại:
\(3x\left(2x-1\right)+1-2x=0\)
\(\Leftrightarrow3x\left(2x-1\right)-\left(2x-1\right)=0\)
\(\Leftrightarrow\left(3x-1\right)\left(2x-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}3x-1=0\\2x-1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{1}{3}\\x=\frac{1}{2}\end{cases}}\)
\(3x^2+3x-6=0\)
\(\Leftrightarrow3x^2+6x-3x+6=0\)
\(\Leftrightarrow\left(3x^2-3x\right)+\left(6x+6\right)=0\)
\(\Leftrightarrow3x\left(x-1\right)+6\left(x-1\right)=0\)
\(\Leftrightarrow\left(3x+6\right)\left(x-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}3x+6=0\Rightarrow3x=6\Rightarrow x=2\\x-1=0\Rightarrow x=1\end{cases}}\)
Vậy x=2 và x=1